SUFI HEALING DAN NEURO LINGUISTIC PROGRAMMING: STUDI TERAPI PADA GRIYA SEHAT SYAFAAT (GRISS) 99 SEMARANG - Mamluatur Rahmah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2019)
This study is about Sufi healing, which focuses on behaviors related to Sufi healing in the prevention of diseases, both physically and non-physically caused by various problems faced by humans. According to the Sufi perspective, the problem is rooted in the heart. Therefore, healing is emphasized in the health of the heart, through takhallī, taḥallī and tajallī with training (riyāḍah) and earnest (mujāhadah) by the murshid or therapist. In this process, therapists use Neuro Linguistic Programming (NLP) as a technique to facilitate the incorporation of Sufi values. This type of research is qualitative. The method of analysis uses descriptive-qualitative. data sourced from GRISS 99 Semarang. The results of this study are the application of the NLP technique as a Sufi healing technique that aims to purify the soul, through takhallī, taḥallī and tajallī, as the key to meaningfulness of life.